AtMYB41 activates ectopic suberin synthesis and assembly in multiple plant species and cell types. (26th August 2014) - Kosma, Dylan K.; Murmu, Jhadeswar; Razeq, Fakhria M.; Santos, Patricia; Bourgault, Richard; Molina, Isabel; Rowland, Owen
Summary Suberin is a lipid and phenolic cell wall heteropolymer found in the roots and other organs of all vascular plants. Suberin plays a critical role in plant water relations and in protecting plants from biotic and abiotic stresses. Here we describe a transcription factor, AtMYB41 (At4g28110), that can activate the steps necessary for aliphatic suberin synthesis and deposition of cell wall‐associated suberin‐like lamellae in both Arabidopsis thaliana and Nicotiana benthamiana. Overexpression of AtMYB41 increased the abundance of suberin biosynthetic gene transcripts by orders of magnitude and resulted in the accumulation of up to 22 times more suberin‐type than cutin‐type aliphatic monomers in leaves. Overexpression of AtMYB41 also resulted in elevated amounts of monolignols in leaves and an increase in the accumulation of phenylpropanoid and lignin biosynthetic gene transcripts. Surprisingly, ultrastructural data indicated that overexpression led to the formation of suberin‐like lamellae in both epidermal and mesophyll cells of leaves. We further implicate AtMYB41 in the production of aliphatic suberin under abiotic stress conditions. These results provide insight into the molecular‐genetic mechanisms of the biosynthesis and deposition of a ubiquitous cell wall‐associated plant structure and will serve as a basis for discovering the transcriptional network behind one of the most abundant lipid‐based polymers in nature.